Loss of Correspondent Banking Relationships in the Caribbean : Trends, Impact, and Policy Options - Alleyne, Trevor (IMF Working Papers; Working Paper ;, 2017)
Banks across the Caribbean have lost important Correspondent Banking Relationships (CBRs). The macroeconomic impact has so far been limited, in part because banks either have multiple relationships or have been successful in replacing lost CBRs. However, the cost of services has increased substantially, some services have been cut back, and some sectors have experienced reduced access. Policy options to address multiple drivers, including lower profitability and risk aversion by global banks, require tailored actions by several stakeholders.